The Workaholic Phenomenon in Student Efforts to Compile Self-Image in a Dramaturgical Perspective - Kezia Ave; Muhammad Wildan Ramadhani (Lenggogeni Data Publishing, 2024)
Students In an era filled with intense competition and competitiveness, students are crucial pillars in social and economic development. They are faced with complex challenges, not only in achieving academic excellence, but also in forming a strong and productive personal identity. Students today are under pressure to meet various targets and unwritten standards, creating an environment where these achievements are key to recognition both from themselves and from their surroundings. They try to form a productive self-image, but in the process often become workaholics. Students often show their productive side to build their self-image aimed at the front page, outside of that they tend to be often exhausted both physically and mentally. The goal of productivity formed as a self-image poses a risk where it will form a weak workforce due to physical and mental fatigue that occurs in the process of forming and maintaining a self-image.